Development of Competency Criteria for Real-Ear Measurement: Findings From a Modified E-Delphi Round 1. - Venkatesan, Bavadharani; Bagatto, Marlene; Moodie, Sheila; Scollie, Susan Diane (American Journal of Audiology, 2026)
Background: Hearing aid verification ensures that appropriate audibility and access to the speech signal are provided to the hearing aid user. Best practice guidelines recommend evidence-based verification measures (on-ear real-ear aided response [REAR] and simulated REAR) to match the hearing aid output with prescribed targets. Skill development for measuring and interpreting REAR involves six stages: novice, advanced, beginner, competent, proficient, and expert. At the competent stage, trainees can perform entrustable professional activities independently, demonstrating sufficient competence for unsupervised practice. Purpose: The purpose of this study was to obtain consensus on key competency criteria expected for audiologists performing hearing aid verification across the lifespan to ensure effective real-ear performance evaluation. Method: A modified e-Delphi technique was used. In the preparatory stage, 54 preselected competency items were categorized into seven domains. In the first round of the survey, expert audiologists rated their level of agreement on a 7-point Likert scale ranging from strongly disagree to strongly agree for each competency. An a priori threshold of 70% was required for consensus. Results: Twenty-nine expert audiologists completed the first survey round. Consensus was achieved for 52 out of the 54 competency items. Competencies related to calibration, equipment setup, and interpretation of REAR had over 90% agreement. Items not reaching initial consensus were revised for Round 2 based on expert feedback. Conclusions: Results from Round 1 and the new consolidated items will be shared in Round 2. This study identifies key competencies for audiologists to perform on-ear and simulated REAR, forming the basis for knowledge, training, and improved clinical outcomes.